Changing organisational design and practices for computer–integrated technologies. (4th August 2014) - Tranfield, David; Smith, Stuart; Ley, Clive; Bessant, John; Levy, Paul
Advanced manufacturing technology, based on elements of computer–integrated manufacturing, offers considerable potential for manufacturers as they confront the challenges of the 1990's environment. In particular, CIM offers new opportunities for meeting both price and non–price objectives within manufacturing strategy, such as flexibility, quality, design and service targets. However, despite the promise offered by the technology, experience to date suggests that there are a number of significant implementation problems which restrict the ability of firms to exploit the full potential of CIM. Of particular interest is the growing evidence of the need for parallel organisational adaptation and development to support such technological change. This paper reports on case study–based research in the United Kingdom aimed at identifying the dimensions of such organisational change and the implications of this for future organisational design strategies.